2013
DOI: 10.1073/pnas.1216091110
|View full text |Cite
|
Sign up to set email alerts
|

Circuit-level input integration in bacterial gene regulation

Abstract: Gene regulatory circuits can receive multiple simultaneous inputs, which can enter the system through different locations. It is thus necessary to establish how these genetic circuits integrate multiple inputs as a function of their relative entry points. Here, we use the dynamic circuit regulating competence for DNA uptake in Bacillus subtilis as a model system to investigate this issue. Specifically, we map the response of single cells in vivo to a combination of (i) a chemical signal controlling the constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
(38 reference statements)
0
18
0
1
Order By: Relevance
“…Higher eukaryotes have mechanoresponsive toggle switches (38). Genetic toggle switches have been analyzed theoretically in systems biology, with models verified using switches constructed in E. coli and Bacillus subtilis (39)(40)(41). These switches settle into one of two bistable states, with a single spike in chemical or thermal cues serving to flip from one state to the other.…”
Section: Discussionmentioning
confidence: 99%
“…Higher eukaryotes have mechanoresponsive toggle switches (38). Genetic toggle switches have been analyzed theoretically in systems biology, with models verified using switches constructed in E. coli and Bacillus subtilis (39)(40)(41). These switches settle into one of two bistable states, with a single spike in chemical or thermal cues serving to flip from one state to the other.…”
Section: Discussionmentioning
confidence: 99%
“…A well-characterized example of FBM is in Bacillius subtilis, in the regulation of competence orchestrated by the transcription factor ComK (van Sinderen et al, 1995). Competence is a cellular state induced by nutrient depletion, but only occurs in a fraction of the B. subtilis population due to oscillating levels of ComK at the single-cell level (Veening et al, 2008;Espinar et al, 2013). In one study, Smits et al removed the external regulation of comK, leaving only positive autoregulation, and showed that ComK levels continued to exhibit bistability.…”
Section: Discussionmentioning
confidence: 99%
“…Signal amplification Higher amplification 9,10,36,[69][70][71][72] Noise attenuation^ Attenuated noise 57,[72][73][74] Information transmission^ Higher transmission 57,[72][73][74] Robustness to changes in parameter values High robustness (low sensitivity) 9,10,36,58,69 Speed of response to changes Rate of adaptation 9,10,29,36,48,71,75 Metabolic cost of circuit Low cost 76,77 *as a general trend; ^ Relevant in the stochastic domains of dynamic behavior. Table S4 -Numerical values of the rate constants of the 19 reactions in the PR models used in the stochastic simulations, represented in Figure 4.…”
Section: Experimental Supportmentioning
confidence: 99%